Localization of TMC1 and LHFPL5 in auditory hair cells in neonatal and adult mice. Issue 6 (26th February 2019) - Li, Xiaofen; Yu, Xiaojie; Chen, Xibing; Liu, Zhengzhao; Wang, Guangqin; Li, Chao; Wong, Elaine Y. M.; Sham, Mai Har; Tang, Jie; He, Jufang; Xiong, Wei; Liu, Zhiyong; et al.
ABSTRACT: The channel that governs mechanotransduction (MT) by hair cells in the inner ear has been investigated intensively for 4 decades, but its precise molecular composition remains enigmatic. Transmembrane channel‐like protein 1 (TMC1) was recently identified as a component of the MT channel, and lipoma HMGIC fusion partner‐like 5 (LHFPL5) is considered to be part of the MT complex and may functionally couple the tip link to the MT channel. As components of the MT complex, TMC1 and LHFPL5 are expected to localize at the lower end of the tip link in hair cells, a notion generally supported by previous studies on neonatal mice. However, the localization of these 2 proteins, particularly in the hair cells of adult mice, remains incompletely elucidated. Because determination of TMC1 and LHFPL5 localization at distinct developmental stages is essential for understanding their function and regulation, we used several approaches to examine the localization of these proteins in neonatal and adult hair cells in the mouse. We report several notable findings: 1 ) TMC1 and LHFPL5 predominantly localize at the tip of the shorter rows of stereocilia in neonatal hair cells, which largely verifies the previously published findings in neonatal hair cells; 2) LHFPL5 persists in the hair bundle of hair cells after postnatal day (P)7, which clarifies the previously reported unexpected absence of LHFPL5 after P7 and supports the view that LHFPL5 is a permanent component in the MT complex; and 3) TMC1 and LHFPL5 remain at the tip of the shorter rows of stereocilia in adult outer hair cells, but in adult inner hair cells, TMC1 is uniformly distributed in both the tallest row and the shorter rows of stereocilia, whereas LHFPL5 is uniformly distributed in the shorter rows of stereocilia. These findings raise intriguing questions regarding the turnover rate, regulation, additional functions, and functional interaction of TMC1 and LHFPL5. Our study confirms the previous findings in neonatal hair cells and reveals several previously unidentified aspects of TMC1 and LHFPL5 localization in more mature hair cells.—Li, X., Yu, X., Chen, X., Liu, Z., Wang, G., Li, C., Wong, E. Y. M., Sham, M. H., Tang, J., He, J., Xiong, W., Liu, Z., Huang, P. Localization of TMC1 and LHFPL5 in auditory hair cells in neonatal and adult mice. FASEB J. 33, 6838–6851 (2019). www.fasebj.org